2017
DOI: 10.2147/copd.s115969
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of eosinophil extracellular trap cell death in COPD: does it represent the trigger that switches on the disease?

Abstract: In spite of the numerous studies on chronic obstructive pulmonary disease (COPD), the cellular and molecular basis of the disease’s development remain unclear. Neutrophils and eosinophils are known to be key players in COPD. Recently, neutrophil extracellular trap cell death (NETosis), a mechanism due to decondensation and extrusion of chromatin to form extracellular traps, has been demonstrated in COPD. However, there is limited knowledge about eosinophil extracellular trap cell death (EETosis) and its role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 33 publications
(42 reference statements)
1
19
0
1
Order By: Relevance
“…The concomitant presence of EETs and NETs in COPD sputum was reported recently ( 25 ). The authors concluded that EETs may contribute to the severity of COPD.…”
Section: Extracellular Traps In Disease Pathologysupporting
confidence: 60%
See 2 more Smart Citations
“…The concomitant presence of EETs and NETs in COPD sputum was reported recently ( 25 ). The authors concluded that EETs may contribute to the severity of COPD.…”
Section: Extracellular Traps In Disease Pathologysupporting
confidence: 60%
“…Similar extracellular traps (ETs) have subsequently been observed from other cells of the innate family members, for example, mast cells ( 22 ), monocytes ( 23 ), tissue macrophages ( 24 ), and eosinophils ( 18 , 25 27 ). Recently, even lymphocytes, key effector cells of the adaptive immune system, were demonstrated to eject ETs in vitro when incubated with serum obtained from systemic erythematous lupus (SLE) patients ( 28 ).…”
Section: Evolution Of Extracellular Traps: Etosismentioning
confidence: 63%
See 1 more Smart Citation
“…Similar to neutrophils, eosinophils also display potent pro-coagulative and disruptive functions. In fact, eosinophil extracellular traps have been evidenced not only in coronary thrombi but also in a variety of inflammatory pathologies [ 25 ]. The presence of eosinophils in zones with MVO in experiments parallels the more severe eosinopenia detected in STEMI patients with MVO.…”
Section: Discussionmentioning
confidence: 99%
“…NET primarily identified, produced by neutrophils to kill microorganisms and to defend against pathogens, are demonstrated to be formed also during inflammatory events, as for example, in cystic fibrosis, thrombosis, and chronic obstructive pulmonary disease . In the last years, the list of diseases in which these neutrophil products are demonstrated to be involved was certainly increased and a key role of NET in non‐infective diseases was recently outlined .…”
Section: Discussionmentioning
confidence: 99%